Could peripheral 5-HT level be used as a biomarker for depression diagnosis and treatment? A narrative minireview - Li, Canye; Cai, Qiming; Su, Zuanjun; Chen, Zhicong; Cao, Jinming; Xu, Feng (Frontiers in Pharmacology, 2023)
The serotonin hypothesis of depression is still influential, but the relationship between peripheral 5- HT levels and depression is still unknown. This review aimed to verify whether peripheral 5-HT levels could be used as a gold biomarker for depression diagnosis and treatment. PubMed and EMBASE were searched using terms appropriate to the area of research. Clinical trials and animal experiments from 1957 to 2022 in the following areas were identified: depression, 5-HT, serotonin and peripheral. 69 clinical trials and 404 animal experiments were searched. 54 studies were included: 6 clinical trials about periphery 5-HT levels in depressive patients compared to normal subjects, 16 clinical trials about changes of peripheral 5-HT levels in patients with depression after drug treatment, 19 animal experiments about CNS 5-HT levels with depression in animal models and 13 animal experiments about peripheral 5-HT levels with depression in animal models. Peripheral 5-HT levels presented three different outcomes before and after antidepressant treatments: increased, decreased and no significant change. In conclusion, changes in peripheral 5-HT levels did not show consistent results among these studies. Peripheral 5-HT level could not be used as a biomarker both for depression diagnosis and for antidepressant efficacy evaluation.